2015
DOI: 10.1111/sltb.12158
|View full text |Cite
|
Sign up to set email alerts
|

Association Between Suicidal Ideation and Exposure to Suicide in Social Relationships Among Family, Friend, and Acquaintance Survivors in South Korea

Abstract: Exposure to suicide in social relationships may be associated with suicidal ideation among survivors. In South Korea, which is known for having the highest suicide rate among OECD countries, exposure to suicide in social relationships can have serious consequences as social relationships are greatly emphasized in the society. The purpose of this study was to examine the association between survivors' suicidal ideation and their exposure to suicide in close relationships. Data collected through a telephone surv… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
17
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 59 publications
3
17
1
Order By: Relevance
“…In line with our main hypothesis, we found a greater SI in patients bereaved through suicide when compared to control participants as assessed with Rorschach test according Exner's System, consistently with recent literature findings on the topic of SI in SSs (4, 5, 1021, 37).…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…In line with our main hypothesis, we found a greater SI in patients bereaved through suicide when compared to control participants as assessed with Rorschach test according Exner's System, consistently with recent literature findings on the topic of SI in SSs (4, 5, 1021, 37).…”
Section: Discussionsupporting
confidence: 92%
“…Recently, Campos et al (13) and Santos et al (19) found that, in a large European sample of SSs, being a strict relative of the suicided person, significantly contributed to the suicide risk. Similar results were found in Asian population: Song et al (37) found that individuals who lost a family member have in their lifetime 4.5 times more probability of SI, whereas if the victim was a friend or an acquaintance the SI probability was, respectively 3.7 times and 2.2 times that of people without such experience.…”
Section: Introductionsupporting
confidence: 81%
See 2 more Smart Citations
“…In this context, it is important to also attend to "suicide survivors"-people who had close social relationships with the suicide victim. Globally, the concept of suicide survivors is widely used to refer to people who experienced the loss of someone close due to suicide -those who have been involuntarily exposed to suicide through the death of a relative, friend, colleague, or neighbor [2,3]. In a broad sense, suicide survivors include all individuals exposed to the suicide of another, but the narrower meaning is usually restricted to close relationships such as family, friends, and neighbors [4].…”
Section: Introductionmentioning
confidence: 99%